Risk Spillover: A New Perspective on the Study of Financing Difficulties for SMEs—Evidence from China - Jinghong Xu (Hindawi Limited, 2021)
Existing studies on the financing difficulties of middle- and small-sized enterprises (SMEs) have neglected the quantitative analysis of SMEs’ risk spillovers to banks. Therefore, taking China as an example, we have analyzed the financing difficulties of SMEs from the perspective of risk spillover. The GARCH time-varying copula-CoVaR model based on the skewed-t distribution was used to measure the risk spillover effects of SMEs on banks. Furthermore, the heterogeneous impacts of risk spillovers on different scale banks were analyzed, including state-owned banks, joint-stock banks, and city commercial banks. The study found that SMEs always have obvious risk spillover effects on banks; it is particularly difficult for SMEs to obtain loans from the largest state-owned banks because in extreme cases, SMEs have the highest risk spillover effects on state-owned banks. The changes in risk spillover effects are attributed to two reasons. One is that the degree of association between SMEs and various banks is different, and the other is that there are varying degrees of risk spillover effects among various banks.